HAMBATAN DALAM MEMBANGUN PEMAHAMAN MODERASI BERAGAMA DI PESANTREN MUSTAFAWIYAH PURBA BARU, MANDAILING NATAL - Datuk, Datuk Imam Marzuki; Santi Hasibuan (AT-TAWASUL, 2025)
This study discusses the obstacles to instilling an understanding of religious moderation in the Mustafawiyah Purba Baru Mandailing Natal Islamic Boarding School. Using a qualitative research approach, and also the theory of Socialization and Social Cognitive. The findings in this study are that obstacles to instilling religious moderation must pay attention to the traditions and values of the Islamic boarding school. And while remaining open to the benefits of modernization that can enrich religious education. Furthermore, a literal understanding of religion, lack of training for teachers, teachers or ustadz. Furthermore, there is the influence of media accessed via smartphones. Efforts to strengthen national insight, students. Certain social and political influences that promote extreme or narrow religious views.